Improving Skills to Manage Household Waste in Wonokromo Urban Village, Surabaya - Dedy Kunhadi; Badriyah Badriyah; Yayah Atmajawati (OJS Universitas Muhammadiyah Gresik, 2018)
Surabaya is one of the cities in Indonesia that has problems on garbage. In handling the garbage, the city government of Surabaya issued a large enough budget to transport the waste to the landfill (TPA). This can be reduced if the waste from the source can be managed properly. Lack of public awareness in RT. 019, RW. 04 Kelurahan Wonokromo Surabaya City in managing household waste, it can be seen from the community disposing of waste is not sorted and do not know how to recycle the waste. By recycling waste into compost, in addition to helping the government in reducing the waste can also green the environment with the resulting compost fertilizer. Community service is done to members of the PKK in RT. 019, RW. 04, Wonokromo urban village of Surabaya, and implemented on April 1 -November 31, 2015. The method used in community service is counseling and training in managing household waste. The result of community service is that most PKK members can sort waste and manage their household waste into compost, and the community environment becomes green from the resulting compost.